Study on Weight Loss and Morphology of Polyester Fiber after Alkali Treatment - Nguyen, Nhat Trinh; Nguyen, Minh Tuan; Do, Thi Hoai; Nguyen, Dieu Linh (Old Journal, 2018)
100% polyester fabric (PET) is mainly used to produce bags and households products. For apparel products, usable properties of 100% PET fabric are restricted because the fabric is toughness and low moisture absorption. To improve the comfort of 100% PET fabric, the fabric is treated by alkali; after alkali treatment the surface structure of polyester fiber is modified, the fabric is smoother and gets better moisture absorption, and looks like silk. The paper investigates simultaneous influence of technological parameters as: treatment temperature, treatment time and alkali concentration to weight loss of 100% PET fabric by Box-Wilson orthogonal experimental arrangement method and uses Design-Experts software to establish experimental regression equation and shows 3D relation of parameters. The results indicated that weight loss of 100% PET fabric after alkali treatment is linear proportional to technological parameters. SEM photographs show micro destroy of fiber surface, destroy degree is depended on alkali treatment. FTIR analysis indicates alkali treatment do not create new chemical bond in PET molecular structure.